Improving the Treatment Tactics of Obstructive Bronchitis Due to Myocarditis in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Obstructive bronchitis is the most common disease among the child population, occupying not the last place in the structure of morbidity among children. The relevance of chronicity, disability and mortality from this morbidity remains. Purpose of the study: to study the effectiveness of nebulizer inhalation with nebutamol and oral levocarnitine for obstructive bronchitis in children against the background of myocarditis. Materials and methods of research. 80 children aged 1 to 10 years with obstructive bronchitis secondary to myocarditis were observed.The patients were divided into 2 groups: Group I 40 patients – children with obstructive bronchitis due to myocarditis, Group II 40 patients – children with obstructive bronchitis. Patients with children with obstructive bronchitis due to myocarditis were divided into 2 subgroups: subgroup Ia of 20 children who received standard therapy and subgroup Ib of 20 children who received nebulizer inhalations of nebutamol and levocarnitine in addition to standard therapy.